Association of Inflammatory Bowel Disease and Acute Anterior Uveitis, but Not Psoriasis, With Disease Duration in Patients With Axial Spondyloarthritis: Results From Two Belgian Nationwide Axial Spondyloarthritis Cohorts. Issue 10 (27th September 2018) - Varkas, Gaëlle; Vastesaeger, Nathan; Cypers, Heleen; Colman, Roos; Renson, Thomas; Praet, Liesbet Van; Carron, Philippe; Raeman, Frank; Devinck, Mieke; Gyselbrecht, Lieve; Corluy, Luc; Piette, Yves; et al.
Abstract : Objective: To determine the link between extraarticular manifestations (EAMs) and baseline characteristics in patients with axial spondyloarthritis (SpA), and to define their potentially differential prognostic value in 2 large, independent Belgian axial SpA cohorts with distinct recruitment periods. Methods: Information on demographic and clinical characteristics and extraarticular manifestations (EAMs) was obtained from patients with axial SpA originating from the (Be)Giant (Belgian Inflammatory Arthritis and Spondylitis) cohort, which includes consecutive axial SpA patients whose data have been collected since 2010, and from the ASPECT (Ankylosing Spondylitis Patients Epidemiological Cross‐sectional Trial) cohort, a Belgian registry of cross‐sectional data collected between February 2004 and February 2005 from consecutive patients with ankylosing spondylitis (AS) or probable AS. Results: Among the 1, 250 Belgian patients studied, disease duration was associated with risk of developing inflammatory bowel disease (IBD), with an increase in risk by 20% per 10 years of disease duration (relative risk [RR] 1.2, P = 0.026), and associated with risk of developing acute anterior uveitis, with an increase in risk by 30% per 10 years of disease duration (RR 1.3, P < 0.001). In the subgroup of 171 newly diagnosed patients with prospective follow‐up data, higher mean C‐reactive protein levels over time were demonstrated in those with acute anterior uveitis or IBD compared to those without EAMs or those with psoriasis alone (each P = 0.01). Conclusion: The risk of developing acute anterior uveitis or IBD, but not psoriasis, in patients with axial SpA seems to increase with disease duration and appears to be linked to a higher cumulative exposure to inflammation, thus providing a possible explanation for the differential structural progression observed in those with axial SpA.